Women's liberation: what's in it for men? - Matthias Doepke; Michèle Tertilt (Institute for the Study of Labor (IZA), 2008)
The nineteenth century witnessed dramatic improvements in the legal rights of married women. Given that these changes took place long before women gained the right to vote, they amounted to a voluntary renouncement of power by men. In this paper, we investigate men's incentives for sharing power with women. In our model, women's legal rights set the marital bargaining power of husbands and wives. We show that men face a tradeoff between the rights they want for their own wives (namely none) and the rights of other women in the economy. Men prefer other men's wives to have rights because men care about their own daughters and because an expansion of women's rights increases educational investments in children. We show that men may agree to relinquish some of their power once technological change increases the importance of human capital. We corroborate our argument with historical evidence on the expansion of women's rights in England and the United States.
urn:nbn:de:101:1-2008040163
Keywords: D13; 330; Women's rights; political economy; human capital; return to education; economic growth; Frauenpolitik; Gleichberechtigung; Männer; Kinder; Frauenbildung; Eigeninteresse; Sozialgeschichte; Großbritannien; USA